The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s1517-74912002000400014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito dose-resposta de uma formulação de dentifrício com concentração reduzida de fluoreto: estudo in vitro

Abstract: The utilization of dentifrices with low fluorine concentration, for children under 6 years of age, has been suggested to reduce the risks of dental fluorosis. However, in order to have anticariogenic potential, the dentifrice should form loosely-bound fluorine (CaF2) on dental enamel. Considering that the formation of CaF2 is a function inversely related to pH, dentifrices with pH 5.5, with 275, 550 and 1,100 ppm F (NaF/silica) were developed in order to assess dose-response effects. A comparison between those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Negri and Cury [2002] also demonstrated that the amount of CaF 2 formed after treatment with an acidic 550-g F/g dentifrice (NaF, pH 5.5) was equivalent to that obtained after use of a commercial 1,100-g F/g dentifrice.…”
mentioning
confidence: 70%
“…Negri and Cury [2002] also demonstrated that the amount of CaF 2 formed after treatment with an acidic 550-g F/g dentifrice (NaF, pH 5.5) was equivalent to that obtained after use of a commercial 1,100-g F/g dentifrice.…”
mentioning
confidence: 70%
“…The concentrations of 150–1,350 ppm F used in the experiment simulates the dilution 1:3 that occurs in the oral cavity [ 38 ] when toothbrushing with toothpastes of low to high fluoride concentration. Therefore, this model could be used to estimate the anti-caries potential of innovative toothpaste formulations with low fluoride concentration [ 46 ] that could be recommended to control enamel caries in children, and formulations with high fluoride concentrations, that have been suggested to control root caries in elderly people [ 19 , 21 , 22 ]. Furthermore, the model could be used to estimate the anti-caries potential of fluoride on the cervical area in adults and elderly people, where dentine is exposed and enamel and dentine are at the same risk of caries.…”
Section: Discussionmentioning
confidence: 99%
“…Cabe ressaltar que o método empregado determina a extração de uma camada superficial do esmalte 9 ou seja, em tese, foi determinada a concentração na superfície. Análises na profundidade do esmalte são possíveis somente in vitro 15 . Ainda que não significativa essa diferença na concentração de F -depositado na forma de CaF 2 na superfície do esmalte, podemos pressupor que fatores individuais como pressão exercida durante a escovação, número e velocidade dos movimentos e capacidade de eliminar o remanescente pela expectoração, poderiam interferir na menor concentração de F -depositada quando da realização da EGF, uma vez que interfeririam no tempo de contato da solução com o esmalte dentário.…”
Section: Métodosunclassified